Technology as a bridge: developing intercultural understanding through a counselling student videoconference. Issue 3 (27th May 2017) - Meekums, Bonnie; Wathen, Cristen C.; Koltz, Rebecca L.
ABSTRACT: The purpose of this research was to explore the experience and implementation of a cross-cultural (UK/USA) student videoconference. Participating students were video recorded while participating in a videoconference between a USA University's class Counselling Theories II and a UK University's class, Becoming a Reflective Practitioner 2A. Students in each location prepared their own topic guide in advance of their participation in a live link-up. The videoconference was transcribed. Both sets of students also engaged in a debrief with their tutors immediately after the conference. The UK debrief was audio recorded and transcribed, adding reflective depth to the main findings from the student videoconference. The three tutor/researchers analysed the video and transcriptions, paying attention both to what was said, and to the embodied engagement between students. Analysis was thematic, with a special focus on the students' use of metaphor. Two key overarching metaphors were identified. The first of these encapsulated an understanding of cultural similarities: Stiff upper lips and Montana cowboys. The second metaphor identified the transformational affective shift in perception of each other: From aliens to neighbours across the pond. Limitations of the research are discussed, and recommendations for future research are made.